2022
DOI: 10.1039/d1sm01382c
|View full text |Cite
|
Sign up to set email alerts
|

Effect of interfacial rheology on drop coalescence in water–oil emulsion

Abstract: Over the last years several studies have been conducted to understand emulsions formation and its behavior. In some applications, the aim is the phase separation of the emulsions through the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 60 publications
0
18
0
Order By: Relevance
“…The oil and the surfactant used in our study are not pure substances but mixtures of various components, some of which are expected to be volatile and of low Mw (Urlaub et al 2019;Grob et al 1991;Abou-Nemeh and Bart 1998). Moreover, SPAN80 has been found to interact strongly with components in other commercially available mineral oils (Botti et al 2022). To assess the possible effect of the multi-component nature of the studied systems on film lifetime distributions, we examined both degassed and not-degassed light mineral oil solutions.…”
Section: Extrinsic Factors Causing Premature Film Rupturementioning
confidence: 99%
“…The oil and the surfactant used in our study are not pure substances but mixtures of various components, some of which are expected to be volatile and of low Mw (Urlaub et al 2019;Grob et al 1991;Abou-Nemeh and Bart 1998). Moreover, SPAN80 has been found to interact strongly with components in other commercially available mineral oils (Botti et al 2022). To assess the possible effect of the multi-component nature of the studied systems on film lifetime distributions, we examined both degassed and not-degassed light mineral oil solutions.…”
Section: Extrinsic Factors Causing Premature Film Rupturementioning
confidence: 99%
“…60 Droplet coalescence is essentially a dilatational process in which the interface becomes stretched during its rupture: Bergeron 80 suggested that differences in foam or emulsion stability can be explained by taking into account the dilatational viscoelastic effects with respect to prevention of thin film thinning. For w/o emulsions stabilized by Span 80, Carvalho and co-workers 48 found that the resistance to coalescence was related to the interfacial dilatational properties for systems with the same interfacial tension. Saigal et al 68 suggested that the stability of emulsions formed by star copolymers was a result of the elastic nature of the adsorbed layer and their high adsorption energy compared to the analogous linear copolymers.…”
Section: Introductionmentioning
confidence: 99%
“…The interfacial properties of adsorbed species play a role in determining their efficacy as emulsion stabilizers. [43][44][45][46][47][48] The interfacial and surface viscoelastic properties of surfactants, [49][50][51][52][53] polymers [51][52][53][54][55][56][57][58][59][60][61][62] or nanoparticles at the air-water or oil-water interface 49,[63][64][65][66][67][68][69] have been studied using interfacial dilatational rheology. 70,71 In this technique, an equilibrated interface is subjected to a sinusoidal or step change deformation [72][73][74] and the resulting change in interfacial tension is used to determine the dilatational moduli, e. This parameter describes how the interfacial tension, g, varies with surface area during deformation (DA/A 0 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 The adsorption method was considered to be an effective and rapid treatment method, and oilabsorbing materials have attracted wide attention because of their convenience and low cost. [7][8][9] The commonly used adsorbents, such as activated carbon, zeolite, 10 mesoporous silica nanomaterials, glass wool, 11 plant fiber, 12 and other adsorbents, could remove organic pollutants from wastewater and the adsorption removal rate reached more than 90%. 3,13 However, the traditional adsorption materials had some limitations in the adsorption rate, oil adsorption and recycling.…”
Section: Introductionmentioning
confidence: 99%